The Influence of Workload, Job Satisfaction, and Communication on the Performance of Support Service Workers at Pertamina Abab Dewa Raja Field - Nurjanah, Rina; Hasmawaty, Hasmawaty; Gunarto, muji (International Journal of Finance Research, 2024)
This study aims to understand and analyze the relationship between the influence of workload, job satisfaction, and communication on the performance of support service workers at Pertamina Abab Dewa Raja Field. The population in this study consists of support service workers (TKJP) selected randomly, involving 70 individuals, with a breakdown of 35 contact support workers and 35 workers from production contracts. The data collection technique involves questionnaires, and the multiple regression analysis technique is processed with statistical software. Data analysis techniques involve data verification, questionnaire management, and data processing: (a) data validity test, (b) data reliability test, (c) multiple linear regression test, and (d) hypothesis testing. The data analysis process used statistical formula applications to facilitate researchers' processing and interpreting data.